ERT geoelectric application to determine the leakage direction of Embung Batur Agung, Karangwetan, Karangmojo District, Gunungkidul Regency, Indonesia - Muhammad Faizal Zakaria; Sari Bahagiarti Kusumayudha; Hanafiah Hamid (International Journal of Advances in Applied Sciences, 2023)
Embung Batur Agung is a source of irrigation for residents around Embung. Depreciation of water in the reservoir occurs due to leakage from the geomembrane layer of the Embung Batur Agung. This study aims to determine the direction of leakage from the reservoir so that appropriate treatment can be carried out. This research was done using hydrogeological analysis and electrical resistivity tomography (ERT) geoelectrical measurements. ERT Geoelectrical measurement uses a dipole-dipole configuration with a spacing of 5 m and 10 m and a line length of 100 m. There are 2 lines in the southwest and southeast of the reservoir. The results of geohydrology analysis, it was found that the aquifer system around the reservoir included in the Gunungsewu aquifer system, and the dynamics of surface groundwater are controlled by faults and fractures. The results of the ERT geoelectrical measurement, there is a low anomaly which can indicate a reservoir leak at 50-60 m on line 1 which is in the southwest of the reservoir. This low anomaly has a vertical pattern as well as there is a fracture which is the cause of the reservoir leak. These low anomaly values range from 4-30 Ωm which can be interpreted as the presence of water that has conductive properties. The results of this study are expected to be used by the local government to handle the leakage of the reservoir.